Pengaruh Perbandingan Terigu dan Pati Garut (Maranta arundinacea L.) Termodifikasi Autoclaving-Cooling Terhadap Karakteristik Mi Basah - Agnes Monika Gandhes Sekarjati; Gusti Ayu Kadek Diah Puspawati; Anak Agung Istri Sri Wiadnyani (Department of Food Science and Technology Study Program, Faculty of Agricultural Technology, Udayana University, 2023)
This study aimed to determine the ratio effect of wheat flour and autoclaving-cooling modified arrowroot starch on the characteristics of wet noodle and to obtain the correct comparison of wheat flour and autoclaving-cooling modified arrowroot starch to produce wet noodle with the best characteristics. The research method used a Randomized Block Design with comparison treatment of wheat flour and autoclaving-cooling modified arrowroot starch consisted in 6 levels (100:0, 90:10, 80:20, 70:30, 60:40, 50:50). The treatment was repeated 2 times to obtain 12 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan’s Multiple Range Test. The result showed that the comparison of wheat flour and autoclaving-cooling modified arrowroot starch has a significant effect (P<0.05) on moisture content, ash content, protein content, elasticity, water absorption, and cooking loss. The best treatment was the 70:30 comparison of wheat flour and autoclaving-cooling modified arrowroot starch with the characteristics 34.59% of moisture content, 0.33% of ash content, 6.12% of protein content, 13,00% of elasticity, 425,26% of water absorption, 11,47% of elasticity, also sensory evaluation color was liked, aroma was liked, texture was chewy and liked, taste was liked, and overall acceptance was liked.